1979
DOI: 10.1111/j.1365-2672.1979.tb01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid and Polar Lipid Composition in the Classification of Cellulomonas, Oerskovia and Related Taxa

Abstract: Strains representing the taxa Cellulomonas, Oerskovia, Brevibacterium fermentans, Corynebacterium manihot and Nocardia cellulans were degraded by acid methanolysis and the non‐hydroxylated fatty acid esters released examined by thin‐layer and gas chromatography. The major fatty acid in all strains was 12‐methyltetradecanoic acid (anteiso C15) which occurred together with other anteiso acids, iso and straight‐chain acids. The fatty acid profiles of the cellulomonads were distinguished by the presence of 13‐carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
544
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 895 publications
(550 citation statements)
references
References 35 publications
6
544
0
Order By: Relevance
“…Strain ST13 T was subjected to chemotaxonomic analysis for its classification in the family Dermacoccaceae, including menaquinones, 13 polar lipids, 17 wholecell sugars 18 and DNA G+C content. 19 Analysis of cellular fatty acids was carried out using the Microbial Identification System version 4.02 (MIDI, Inc., Newark, DE, USA), 20 and the results were compared with the ACTINO library in the Microbial Identification System.…”
Section: Chemotaxonomic Analysismentioning
confidence: 99%
“…Strain ST13 T was subjected to chemotaxonomic analysis for its classification in the family Dermacoccaceae, including menaquinones, 13 polar lipids, 17 wholecell sugars 18 and DNA G+C content. 19 Analysis of cellular fatty acids was carried out using the Microbial Identification System version 4.02 (MIDI, Inc., Newark, DE, USA), 20 and the results were compared with the ACTINO library in the Microbial Identification System.…”
Section: Chemotaxonomic Analysismentioning
confidence: 99%
“…The sum of the 21 PLFAs relative to the internal standard was also used as a relative measure of total biomass (totPLFA). The PLFA a15:0, which is widely found in Gram+ bacteria from the genus Cellulomonas (Lednická et al 2000; Minnikin et al 1979), was used as an indicator for cellulose-decomposing bacteria. The PLFA 18:2ω6,9 was used as an indicator for fungal biomass, with that of 18:1ω9 as additional evidence of fungal origin, although it is not a perfect indicator of fungi (Frostegård et al 2011).…”
Section: Phospholipid Fatty Acid and Ergosterol Analysismentioning
confidence: 99%
“…The isolate contained dihydrogenated menaquinones with eight isoprene units [MK-8(H 2 )] as the major isoprenologue and minor amounts of MK-6(H 2 ) and MK-7(H 2 ). Polar lipids were extracted by the method of Minnikin et al (1979) and identified according to Collins & Jones (1980). Strain Ca11 T exhibited a lipid pattern consisting of diphosphatidylglycerol (DPG), phosphatidylethanolamine (PE), phosphatidylinositol (PI), one unknown phospholipid (PL) and an unknown glycolipid (GL) and traces of phosphatidylinositol mannosides (PIM) (Fig.…”
mentioning
confidence: 99%